Suite for Human Nature - Lampert, Diane; Puybaret, Eric (New York Atheneum Books For Young Readers, 2016)
Looks at how the mischievous children of Mother Nature are cared for by the worlds humans, who gradually absorb their charges wild personality traits before learning to temper them with love.
"Based on a musical composition by Diane Charlotte Lampert and Wynton Marsalis."
"A Caitlyn Dlouhy book."
Keywords: Human behavior -- Fiction; Human behavior -- Fiction